TERAPI FARMAKOLOGI INSOMNIA - Sulistiana Dewi,; Shinta Brisma,; Dian Budianti Amalina, (Nusantara Hasana Journal, 2025)
Insomnia is a common sleep disorder characterized by difficulty initiating sleep, maintaining sleep, or achieving restorative sleep, leading to impaired daytime functioning. Pharmacological therapy is often considered when non-pharmacological interventions fail to provide adequate relief. Several classes of medications are used to manage insomnia, including benzodiazepines, non-benzodiazepine receptor agonists (Z-drugs), melatonin receptor agonists, orexin receptor antagonists, antidepressants with sedative properties, and antihistamines. Each class varies in its mechanism of action, onset, duration of effect, and risk profile. While pharmacological therapy can be effective for short-term symptom relief, inappropriate or prolonged use may lead to tolerance, dependence, cognitive impairment, or residual daytime sedation. Therefore, medication selection should be tailored to the patient’s clinical profile, comorbidities, and sleep patterns. Integrating pharmacological therapy with behavioral approaches such as cognitive behavioral therapy for insomnia (CBT-I) is recommended to achieve sustainable long-term outcomes.